Repercussões da covid-19 na primeiríssima infância: percepções de famílias em contextos de pobreza sobre o crescimento e desenvolvimento infantil - Pacheco, Ingrid (Universidade Federal de São Carlos, 2024)
Early childhood is a fundamental period for the process of child growth and development. This process may have been affected by the Covid-19 pandemic due to the implications of social distancing, which caused changes in services, support networks and the home environment. These impacts on children and their families were amplified in contexts of poverty. Objective: To understand the perceptions of families in poverty contexts about the repercussions of the covid-19 pandemic in early childhood. Method: Qualitative research anchored in the Bioecological Theory of Human Development framework. It was carried out in two municipalities in the interior of the state of São Paulo, with approximately 250 thousand inhabitants, in two Primary Health Care units. The participants in this study were family members, following the inclusion criteria: (1) being a caregiver for a child of 1 to 3 years; and (2) living in a context of poverty. For data collection, medical records analysis and semi-structured interviews were used. The data collection period was from May to June 2023. The data was analyzed inductively through reflective thematic analysis. The research was approved by the Human Research Ethics Committee (CAAE: 67340323.5.0000.5504). Results: There were 25 participants, 20 mothers and 5 grandmothers. Two final themes emerged. The first final theme was titled “'A hell of a hassle, only at home' – repercussions of the pandemic on the family microsystem”, revealing pandemic repercussions on reproductive planning, the pregnancy-puerperal cycle, family configuration and the support network, with emphasis on care by the woman, mother or grandmother. In the second theme entitled “'We had several losses due to COVID-19' – mesosystem, exosystem and macrosystem in pandemic times and contexts of poverty”, the interrelationships between the microsystems in which the child is inserted were presented, triggered from the environment familiar. Mesosystemic relationships, especially with the daycare center and the PHC unit, were essential and at times challenging. The process of growth and development during the pandemic was crossed by experiences of mourning, contexts of worsening income and changes in work routines. Furthermore, it was influenced by beliefs, values, religions, public policies and political context. Final considerations: This study allowed a broader view of growth and development in early childhood, in the light of bioecological theory. The incorporation of this knowledge can mitigate the effects of the pandemic period, through short, medium and long-term actions in the organization of services and practices, especially in education, social assistance and health. DESCRIPTORS: Child Development, Growth, COVID-19, Poverty, Nursing, Qualitative Research.
Repercussions of covid-19 in early childhood: perceptions of families in poverty about child growth and development
Keywords: Desenvolvimento Infantil; Crescimento; COVID-19; Pobreza; Enfermagem; Pesquisa Qualitativa; Child Development; Growth; COVID-19; Poverty; Nursing; Qualitative Research; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM DE SAUDE PUBLICA; CIENCIAS DA SAUDE::ENFERMAGEM